Vortioxetine for the treatment of major depressive disorder. Issue 6 (November 2014) - Tritschler, Laurent; Felice, Daniela; Colle, Romain; Guilloux, Jean-Philippe; Corruble, Emmanuelle; Gardier, Alain Michel; David, Denis Joseph
<x xml:space="preserve">Abstract</x> Vortioxetine (Brintellix®, 1-[2-(2, 4-dimethylphenyl-sulfanyl)-phenyl]-piperazine) is a multimodal antidepressant targeting the 5-HT1A, 5-HT1B, 5-HT1D, 5-HT3, 5-HT7 receptors and the serotonin (5-HT) transporter (5-HTT). Vortioxetine administration induces antidepressant- and anxiolytic-like effects, and can enhance cognitive performance in rodents. Several clinical trials have reported the efficiency and a satisfactory tolerability of vortioxetine treatment in depressed patients. Remarkably, vortioxetine has a specific positive impact on cognitive symptoms in depressed patients. Overall, vortioxetine is an efficacious antidepressant drug for the treatment of patients with a major depressive episode and has a unique mechanism of action offering a new therapeutic option.